Assessment of ground water quality influenced by sea water ingression in part of Sundarbans and its suitability for crop production - SI, SISIR KUMAR (Journal of Soil and Water Conservation, 2020)
The objective of the study was to identify the ground water potential zones in part of Sundarbans for irrigation by assessing the impact of ground water contamination with saline water. The study area is divided into four parts based on situation i.e. (I) Island part adjacent to Bay of Bengal (II) Easter part surrounded by saline rivers, tidal creeks etc. (III) Inland portion closed to Bay of Bengal and (IV) Inland portion away to Bay of Bengal. Ground water samples were collected from six different layers below ground level i.e. 40-60ft, 260-340ft, 400-480ft, 600-680ft, 800-880ft and >1000ft and pH, EC, Ca, Mg, Na were analyzed in laboratory. The analytical results shows that the ground (800-880ft BGL) of the study area are grouped in good category, ground water (400-480 ft BGL) in parts I & II are high SAR-saline category, in part III is high SAR – marginally saline water and in Part IV is only marginally saline water category based on EC and SAR. The concentration of salt (i.e. EC values) and relative ionic concentration of Na (i.e. SAR value) are used to identify the contamination of saline water with fresh water along depth as well as in distance from saline water sources